Macroalgae of the sandy cays of Alacranes Reef: Gulf of Mexico - Torruco, Daniel; González-Solis, M. Alicia (Journal of Phytology, 2024)
In the summer of 2018, a field trip to the five sandy cays on the leeward edge of the Alacranes reef was made: Pájaros Island, Chica Island, Pérez Island, Muertos or Desertora Island and Desterrada Island. The total area recorded for the 5 islands is 530,407 m2, representing 1.7% of the reef area. In the keys, an extensive collection of macroalgae was carried out in the supralittoral zone (0-80 cm), mesolittoral (81-140 cm), and beginning of the infralittoral zone (150-330 cm). All keys have a maximum height of 3-4 m. A total of 175 species, 4 growth forms, 8 varieties, and one subspecies were recorded. The sandy cays of this reef have been recognized as important nesting areas for turtles and seabirds, hence the importance of their description for their conservation. To try to understand its dynamics, the database obtained was subjected to a divisive classification analysis considering 19 attributes including substrate, protection, reproductive status, and depth. The system reached a total diversity of 425.99 beles Ind-1. The analysis presents that depth and substrate are mainly responsible for the largest drops in information in the system. The spatial analysis given by a biplot analysis shows an ecotonal continuum from the center of origin to the right, influenced by the substrate and by wave protection. This analysis gives an explained variance of 60.03% in the first three components. The high diversity of flora recorded in this work can be an important support for protecting and conserving the reef.